7‐2: High‐contrast Encoding Method for Amplitude‐only Computer Generated Hologram. Issue 1 (30th May 2018) - An, Jungkwuen; Shin, Bongsu; Lee, Chang-Kun; Choi, Chil-Sung; Yoo, Chorong; Sung, Geeyoung; Kim, Hojung; Song, Hoon; Chung, Jae-Seung; Seo, Juwon; Won, Kanghee; Lee, Sung-Hoon; et al.
Abstract : The new encoding methods are proposed and demonstrated for amplitude‐only computer‐generated hologram (CGH). Traditionally, the amplitude‐only encoding method proposed by Burch, has been used over 50 years, because it is the deterministic solution for generating an ideal hologram added by its conjugated hologram. Since the amplitude‐only hologram cannot represent negative values, the result of Burch's encoding should always be added by some values, so that none of data is less than zero. It means that the electric‐field of zero amplitude mapped into the medium gray level in a spatial light modulator (SLM). In ideal holographic display, it does not cause any problem on reconstructing holograms, but the medium gray level actually adds the noise at the practical holographic display. We introduce the encoding methods which can map the zero amplitude into the zero gray level. These encoding methods can increase the contrast ratio of an amplitude‐only hologram by reducing unnecessary scattering and stray lights.